2016
DOI: 10.1007/s11745-016-4154-9
|View full text |Cite
|
Sign up to set email alerts
|

4‐Hydroxyderricin, as a PPARγ Agonist, Promotes Adipogenesis, Adiponectin Secretion, and Glucose Uptake in 3T3‐L1 Cells

Abstract: Adipocyte differentiation plays a pivotal role in maintaining the production of small-size adipocytes with insulin sensitivity, and impaired adipogenesis is implicated in insulin resistance. 4-Hydroxyderricin (4-HD), a phytochemical component of Angelica keiskei, possesses diverse biological properties such as anti-inflammatory, antidiabetic, and antitumor. In the present study, we investigated the effects of 4-HD on adipocyte differentiation. 4-HD promoted lipid accumulation in 3T3-L1 cells, upregulated both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Through the mechanistic study, it was determined that PCW increased adiponectin and reduced leptin. These markers are considered as inflammatory modulators, known to play a crucial role in insulin sensitivity and body energy balance . Adiponectin is predominately produced by adipocytes and directly sensitizes cells to insulin, and its levels are lower in insulin resistance and diabetes than in healthy individuals .…”
Section: Discussionmentioning
confidence: 99%
“…Through the mechanistic study, it was determined that PCW increased adiponectin and reduced leptin. These markers are considered as inflammatory modulators, known to play a crucial role in insulin sensitivity and body energy balance . Adiponectin is predominately produced by adipocytes and directly sensitizes cells to insulin, and its levels are lower in insulin resistance and diabetes than in healthy individuals .…”
Section: Discussionmentioning
confidence: 99%
“…A potential mechanism for the effect of EPA to increase adiponectin secretion from canine adipocytes is the upregulation and activation of peroxisome proliferator-activated receptor-γ (PPARγ). Adiponectin production increases with higher levels of expression and activation of PPARγ (Bouskila, Pajvani, & Scherer, 2005;Li et al, 2016;Maeda et al, 2001). In dogs, increased expression of adiponectin in adipocytes differentiated in culture (Ryan et al, 2010) and increased secretion of adiponectin from mature (Mazaki-Tovi et al, 2016) adipocytes have been demonstrated in response to PPARγ agonists.…”
Section: Discussionmentioning
confidence: 99%
“…It is critical in regulating fatty acid uptake, β-oxidation of fatty acids, ketogenic effects, bile acid synthesis, and triglyceride conversion [44], and PPAR-α signaling inhibits lipid accumulation and subsequent oxidative stress. PPARγ is another member of the PPAR family that is an essential transcription factor in regulating lipid metabolism [45,46]. It participates in fat metabolism and promotes synthesis, transport, and lipid deposition by regulating the transcription of lipid metabolism-related genes [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ is another member of the PPAR family that is an essential transcription factor in regulating lipid metabolism [45,46]. It participates in fat metabolism and promotes synthesis, transport, and lipid deposition by regulating the transcription of lipid metabolism-related genes [45,46]. In addition, PPAR-γ acts as a key factor in early adipocyte differentiation and it promotes the expression of C/EBP-α, and then they work together to induce adipocyte differentiation and lipid deposition [47,48].…”
Section: Discussionmentioning
confidence: 99%